2016
DOI: 10.15244/pjoes/60860
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nitrous Oxide Emissions Resulting from Nitrogen Addition and Increased Precipitation in an Alpine Meadow Ecosystem

Abstract: The effects of nitrogen (N) addition and increased precipitation on nitrous oxide (N 2 O) emissions in alpine meadow ecosystems are still unclear. In this study, we measured N 2 O fluxes on the Tibetan plateau under interactions of moderate atmospheric N deposition and increased precipitation using a closed chamber method. Under all applied treatment conditions, the alpine meadow ecosystem acted as a source of N 2 O. The N 2 O emission rate reached a maximum of 74.83±14.40 μg m -2 h -1, with a significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
2
2
0
1
Order By: Relevance
“…However, the corresponding 95% CI of estimates in this meta-analysis was much smaller than that of Homyak et al (2017;−0.53 to −0.19 vs. −1.38 to −0.15), providing a more well-constrained estimate of how precipitation regulates N 2 O production globally. In contrast to the effect of decreased precipitation, N 2 O emission was significantly promoted by increased precipitation (Figure 2c), which is in agreement with most previous observations Du, Guo, Cao, & Li, 2016;Liu et al, 2015;Zhang, Hou, Guo, Li, & Xu, 2017). Together with the consistent response of N 2 O emission to increased and decreased precipitation regardless of biomes, treatment methods and seasons (Figure 2b,c), as well as the strong positive relationship between the effect sizes of N 2 O versus soil moisture (Figure 3c), we highlight that N 2 O emissions from terrestrial ecosystems were strongly regulated by soil water availability.…”
Section: N 2 O Emission Under Changed Precipitation Regimessupporting
confidence: 93%
“…However, the corresponding 95% CI of estimates in this meta-analysis was much smaller than that of Homyak et al (2017;−0.53 to −0.19 vs. −1.38 to −0.15), providing a more well-constrained estimate of how precipitation regulates N 2 O production globally. In contrast to the effect of decreased precipitation, N 2 O emission was significantly promoted by increased precipitation (Figure 2c), which is in agreement with most previous observations Du, Guo, Cao, & Li, 2016;Liu et al, 2015;Zhang, Hou, Guo, Li, & Xu, 2017). Together with the consistent response of N 2 O emission to increased and decreased precipitation regardless of biomes, treatment methods and seasons (Figure 2b,c), as well as the strong positive relationship between the effect sizes of N 2 O versus soil moisture (Figure 3c), we highlight that N 2 O emissions from terrestrial ecosystems were strongly regulated by soil water availability.…”
Section: N 2 O Emission Under Changed Precipitation Regimessupporting
confidence: 93%
“…Our results showed that precipitation changes and AMF were critical factors to affect soil N 2 O emissions from the semiarid grassland ecosystem. Soil moisture had remarkably positive effects on soil N 2 O emission, which is in agreement with most previous observations in grassland ecosystems ( Zhang and Han, 2008 ; Du et al, 2016 ; Li et al, 2018 ). Li et al (2020) reported that N 2 O emission had been suppressed by 31% by precipitation decrease and increased by 55% in precipitation increase conditions.…”
Section: Discussionsupporting
confidence: 92%
“…要工具, 该模型认为氮(N)和磷(P)是限制植物生长 的重要元素, 外源氮和磷添加能促进植物生长, 提 高植物生产力(Aber et al, 1989;Jung et al, 2011;Du et al, 2016)。传统观点认为, 在热带和亚热带等低 纬度地区, 树木生长受磷限制, 而暖温带和寒温带 等中高纬度区域, 树木生长主要受氮限制 (Magnani et al, 2007;Vitousek et al, 2010)。在模拟施肥实验 中, 前人主要通过监测树木生物量的变化来探究限 制元素对树木生长的影响 (Gundersen et al, 1998;Wright & Rasmussen, 1998;Jefts et al, 2004;Magill et al, 2004)。由于大径级树木的地上生物量对群落 生物量的贡献度要大于小径级树木, 以前的研究往 往忽视了限制元素对小径级树木生长的影响 (Li et al, 2018)。其次, 传统限制模型主要从群落水平研 究树木生长对限制元素的响应情况, 而忽略了不同 物种的响应(Aber et al, 1995;Matson et al, 2002;Solberg et al, 2009;de Vries et al, 2014) (Gilliam, 2006;鲁显楷等, 2008)。 另一方 面, 氮添加会造成土壤酸化, 打破土壤中的元素平 衡 (Nadelhoffer et al, 1999), 致使对土壤环境变化敏 感的植物竞争力降低, 生长受抑制甚至消失。 相关研究表明, 温带森林植物生长对氮添加的 响应可能较慢, 一般需要5年以上的时间 (Gundersen et al, 1998;Kjonaas et al, 1998) (Stevens, 2004;Reidsma et al, 2006) 。 Fig. 4 Relationships of relative growth rate (RGR) of Quercus wutaishanica and trees at community level with soil total carbon (TC), total nitrogen (TN) and total phosphorus (TP) content in Mt.…”
Section: 元素限制模型是预测全球植被生产力变化的重unclassified